ANALISIS PENGARUH VARIABEL MAKROEKONOMI DI MASA PANDEMI VIRUS COVID-19 TERHADAP JUMLAH PENERIMAAN ZAKAT DI BAZNAS - S Khajat, Dwi Supriyanto; Munawar Ismail (Islamic Economics and finance in Focus, 2024)
The main purpose this research was carried out is to demonstrate the impact caused by macroeconomic variables including Gross Domestic Product (GDP), Inflation and Gold Prices towards the amount of zakat reception collected by the National Amil Zakat Agency throughout the time of the Covid-19 pandemic 2020-2023 period of time in Indonesia. This research utilizes a quantitative approach to estimate the research data in order to discover causality relationships between independent variables (DGP, Inflation, Gold Price) and dependent variable (Zakat Receipt). Quantitative data is the data type used in this research and the source of data uses secondary data. Autoregressive Distributed Lag (ARDL) is the approach method used in this research. The estimation results appear that independent variable Gross Domestic Product possess a positive impact on Zakat Receipts at BAZNAS during the Covid-19 pandemic, meanwhile Inflation and Gold Prices possess a negative impact on Zakat Receipts at BAZNAS during the Covid-19 pandemic.